Agrafiotis, Panagiotis - (:unkn) unknown (My University, 2026)
Panagiotis Agrafiotis is a researcher in the area of underwater 3D modelling and mapping in the Photogrammetric Vision Lab of the department of Civil Engineering and Geomatics in Cyprus University of Technology while he is cooperating with the Lab. of Photogrammetry and the ICCS of National Technical University of Athens. He holds a Diploma in Rural and Surveying Engineering and a M.Sc. in Geoinformatics, both from the National Technical University of Athens (NTUA). During his studies, he earned two D. Thomaidis Award from Thomaidis Foundation, one for his paper Documentation of a submerged monument using improved two media techniques (IEEE Computer Society), an ISPRS Foundation Travel Grant and a distinction for his Diploma Thesis entitled Development of two-media photogrammetric techniques for the geometric documentation of monuments. The last 4 years he worked in various research projects (5 EU funded and 7 GR+EU funded) with the responsibility of applied Computer Vision algorithms design, Laser Scanning and Cameras Calibration as well as person detection and tracking for survivor localisation. Furthermore his research often deals with the creation of accurate 3D models through Structure From Motion, Structured Light and Laser Scanner techniques. Two-media (through water) and underwater photogrammetry are constantly within his intense interests. Recently he served as a reviewer for MDPI Sensors (ISSN 1424-8220; CODEN: SENSC9) Special Issue "Sensors and Techniques for 3D Object Modeling in Underwater Environments". He is currently the secretary of the ISPRS WG II/9: Underwater Data Acquisition and Processing